The Inhibitory Effect of Clindamycin on Lactobacillus in vitro - Alla Aroutcheva; Jose A. Simoes; Susan Shott; Sebastian Faro (Hindawi Limited, 2001)
Objective: To evaluate the in vitro effect of varying concentrations of clindamycin on Lactobacillus spp.